KEMUNCULAN ISLAMIC HOMESCHOOLING DAN KORELASINYA DENGAN KEBANGKITAN KELAS MENENGAH MUSLIM DI INDONESIA (STUDI KASUS HOMESCHOOLING GROUP KHOIRU UMMAH) - Ichsan W. Saputro (EL-TARBAWI, 2018)
In the 21st century there are changes that are quite interesting in the world of education in Indonesia. There is a new pattern in the Indonesia Islamic educational maps have not been much researched, namely the emergence of home school education using Islam as a basis in the development of the lesson that device. Presence of school house in Indonesia is a response not to satisfy the wishes of Muslim activists in Indonesia in institutional Islamic existed previously good boarding school, madrassa, or school, and disappointment over the current globalization of the bring bad impact on the planting characters of the learners. The presence of a school House that was initiated by Muslim activists in Indonesia can be meant as an attempt to offer alternative education present in the face of the global era. One of the highlights for school networking is scrutinized under a single coordination Khoiru Ummah Foundation builders of civilization (KUPP) Homeschool Group named Ummah Khoiru. Mechanically, this research is qualitative research using a philosophical approach. The methods used for data collection may include interviews, observations, and documentation. Basically this article seeks to examine the existence of a group of middle-class Muslims in Indonesia are being buffer existence HSG Khoiru Ummah. Keywords: Islamic homeschooling